2023
DOI: 10.3390/foods12244465
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Hyperuricemia: Pathogenesis, Potential Therapeutic Role of Bioactive Peptides, and Assessing Bioactive Peptide Advantages and Challenges

Yanchao Chen,
Jing Yang,
Qinchun Rao
et al.

Abstract: Hyperuricemia is a medical condition characterized by an elevated level of serum uric acid, closely associated with other metabolic disorders, and its global incidence rate is increasing. Increased synthesis or decreased excretion of uric acid can lead to hyperuricemia. Protein peptides from various food sources have demonstrated potential in treating hyperuricemia, including marine organisms, ovalbumin, milk, nuts, rice, legumes, mushrooms, and protein-rich processing by-products. Through in vitro experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…While some animal and plant proteins show better uric-acid-lowering effects. Previous studies have found that dietary peptides mainly play a role in reducing UA by inhibiting XOD activity, regulating the expression level of UA transporters, and regulating intestinal microbiota [33]. Animal and plant protein hydrolysates also play a significant role in reducing UA, such as walnut protein hydrolysate [34], tuna protein hydrolysate [35], and whey protein hydrolysate [36].…”
Section: Helps Reduce High Uric Acidmentioning
confidence: 99%
“…While some animal and plant proteins show better uric-acid-lowering effects. Previous studies have found that dietary peptides mainly play a role in reducing UA by inhibiting XOD activity, regulating the expression level of UA transporters, and regulating intestinal microbiota [33]. Animal and plant protein hydrolysates also play a significant role in reducing UA, such as walnut protein hydrolysate [34], tuna protein hydrolysate [35], and whey protein hydrolysate [36].…”
Section: Helps Reduce High Uric Acidmentioning
confidence: 99%
“…Uric acid synthesis involves a variety of enzymes, including xanthine XOD as the key enzyme in the body of uric acid production, purine nucleoside phosphorylase PNP catalyzed creatinine catabolism to produce hypoxanthine to further catalyze the oxidation of intermediate products xanthine, and ultimately xanthine oxidation into uric acid. When XOD activity is dysregulated, the higher activity of XOD will accelerate the catalytic oxidation of hypoxanthine and xanthine, resulting in a continuous increase in uric acid levels and hyperuricemia ( Chen et al, 2023 ). XOD catalyzes the oxidation and hydroxylation of hypoxanthine and xanthine to uric acid, generating reactive oxygen species such as superoxide anion and hydrogen peroxide at the flavin center.…”
Section: Pathogenesis Of Hyperuricemiamentioning
confidence: 99%
“…This imbalance in uric acid levels increases the likelihood of developing gout in individuals with HUA [ 2 ]. Generally, male patients are more likely than female patients, and the age of patients tends to be younger [ 3 , 4 ]. HUA is also accompanied by complications such as gout [ 5 ], chronic kidney disease [ 6 ], obesity [ 7 ], diabetes [ 8 ], and hypertension [ 9 ].…”
Section: Introductionmentioning
confidence: 99%